Pemeriksaan Golongan Darah Sistem ABO Metode Slide dengan Reagen Serum Golongan Darah A, B, O - Oktari, Anita; Silvia, Nida Daeninur (Jurnal Teknologi Laboratorium, 2016)
The standard examination blood type was performed using a reagent that actually less economical. This research in order to determine whether serum blood type can be used as a reagent blood type. It has been already conducted research antibodies in the serum of blood type A, B, and AB. Each serum would reacted with antigent in the blood, indicated by the agglutination. The research method was experimental by performing blood type with drops of serum in the blood type A, B and AB then saw the grade agglutination. The data obtained were processed statistically using Kruskal Wallis. The result showed serum A, B, and O can be used as a substitute reagents alternative anti – A, anti – B, and anti – AB in determining blood type. Based on analysis, quality clotting produced by serum aglutination is not same with the reagent anti – A, anti – B, and anti – AB in determining blood type.